2007
DOI: 10.7326/0003-4819-146-6-200703200-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treatment Strategies in Early Rheumatoid Arthritis

Abstract: Currently available antirheumatic drugs can be highly effective in patients with early rheumatoid arthritis in a setting of tight disease control. Initial combination therapies seem to provide earlier clinical improvement and less progression of joint damage, but all treatment strategies eventually showed similar clinical improvements. In addition, combination therapy can be withdrawn successfully and less treatment adjustments are needed than with initial monotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
237
1
17

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 408 publications
(267 citation statements)
references
References 24 publications
12
237
1
17
Order By: Relevance
“…The results from the BeSt and SWEFOT (Swedish Farmacotherapy) trials indicate that step-up therapy using sulfasalazine (SSZ) and hydroxychloroquine (HCQ) in these patients is inferior to the addition of a TNF inhibitor. 60,74,75 In contrast, the results of the TEAR trial suggest that step-up treatment using SSZ and HCQ is comparably effective to step-up etanercept therapy in both clinical response and radiographic outcomes. 65,66 To mitigate this apparent contradiction, we have considered data regarding the probability of remission at 1 year on the basis of absolute disease activity at 3 months.…”
Section: Critical Time Pointmentioning
confidence: 97%
See 3 more Smart Citations
“…The results from the BeSt and SWEFOT (Swedish Farmacotherapy) trials indicate that step-up therapy using sulfasalazine (SSZ) and hydroxychloroquine (HCQ) in these patients is inferior to the addition of a TNF inhibitor. 60,74,75 In contrast, the results of the TEAR trial suggest that step-up treatment using SSZ and HCQ is comparably effective to step-up etanercept therapy in both clinical response and radiographic outcomes. 65,66 To mitigate this apparent contradiction, we have considered data regarding the probability of remission at 1 year on the basis of absolute disease activity at 3 months.…”
Section: Critical Time Pointmentioning
confidence: 97%
“…57 This conclusion is supported by a 2010 Cochrane systematic review that emphasized lack of evidence of a statistically significant advantage for initial combination therapy using MTX and other conventional DMARDs over monotherapy with MTX. 58 A [59][60][61][62][63][64] The results of these studies suggest that the combination of MTX with a TNF inhibitor or CTLA-4:Ig (abatacept) has greater efficacy than MTX monotherapy insofar as both clinical and radiographic outcomes are concerned.…”
Section: Treatment Approach Initial Treatment Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent indirect comparison network meta-analysis indicated that the effects of combination treatments with and without biologic agents might have similar properties to reduce radiographic joint destruction (2). Until recently, only 1 randomized controlled trial (RCT) directly supported this hypothesis (3,4). The 4 most sold drugs in the world with regard to sales (but not defined daily doses) are biologic agents primarily indicated for RA (adalimumab, infliximab, rituximab, and etanercept).…”
Section: Introductionmentioning
confidence: 99%